A de Novo ZMIZ1 Pathogenic Variant for Neurodevelopmental Disorder With Dysmorphic Facies and Distal Skeletal Anomalies - Lu, Guanting; Ma, Liya; Xu, Pei; Xian, Binqiang; Wu, Lianying; Ding, Jianying; He, Xiaoyan; Xia, Huiyun; Ding, Wuwu; Yang, Zhirong; Peng, Qiongling (Frontiers in Genetics, 2022)
Background: Neurodevelopmental disorder with dysmorphic facies and distal skeletal anomalies (NEDDFSA) is a rare syndromic disorder characterized by global neurodevelopmental delay, early-onset hypotonia, poor overall growth, poor speech/language ability, and other common phenotypes such as eye anomalies, joint hypermobility, and skeletal anomalies of the hands and feet. NEDDFSA is caused by heterozygous mutations in the ZMIZ1 gene on chromosome 10q22 with autosomal dominant (AD) mode of inheritance. All the 32 reported cases with mutations in ZMIZ1 gene had genetic background in European, Caucasian, Hispania, North African and Southeastern Asian. Till now, there have no reports of Chinese patients with ZMIZ1 mutations. Methods: A 5-year-old girl was found to have the characteristic phenotypes of NEDDFSA. Array-Comparative Genomic Hybridization (array-CGH) and whole exome sequencing (WES) were applied for the trio of this female patient. Sanger sequencing was used to verify the selected mutations. The comprehensive molecular analysis was carried out by protein structure prediction, evolutionary conservation, motif scanning, tissue-specific expression, and protein interaction network to elucidate the pathogenicity of the identified ZMIZ1 mutations. Results: The karyotype was 46, XX with no micro-chromosomal abnormalities identified by array-CGH. 20 mutations were identified in the female patient by WES. A de novo heterozygous missense mutation (c.2330G>A, p.Gly777Glu, G777E) was located in the exon 20 of ZMIZ1. No mutations of ZMIZ1 were identified in the non-consanguineous parents and her elder healthy sister. It was predicted that the G777E was pathogenic and detrimental to the spatial conformation of the MIZ/SP-RING zinc finger domain of ZMIZ1. Conclusion: So far, only 4 scientific articles reported deleterious mutations in ZMIZ1 and most of the cases were from Western countries. This project is the first report about a Chinese patient with ZMIZ1 mutation. It will broaden the current knowledge of ZMIZ1 mutations and variable clinical presentations for clinicians and genetic counselors.